Using A Social-ecological Regime Shift Approach to Understand the Transition from Livestock to Game Farming in the Eastern Cape, South Africa - Therezah Achieng; Kristine Maciejewski; Michelle Dyer; Reinette Biggs (Land, 2020)
This study explored the shift in land use from livestock farming to game farming in the Eastern Cape, South Africa, from a social-ecological regime shift perspective. A regime shift can be defined as a large, persistent change in the structure and function of the intertwined social and ecological components of a landscape. This research focused on the Amakhala game reserve as a case study to understand how the shift affected the provision of ecosystem services and human wellbeing. We used remote sensing techniques to quantify changes in vegetation and found evidence of vegetation recovery following the shift. We then conducted interviews with both landowners and farmworkers and used participatory mapping to understand their perceptions of the main drivers and social-ecological impacts of the shift in land use. Social narratives revealed stark differences in different stakeholders’ perceptions, highlighting that the change in land use had varied implications for, and were perceived differently by, different stakeholders. Farmworkers emphasized changes in social structures that weakened community bonds and erased valued connections to the land. At the same time, they increased employment of women, skills development, and increased wages as benefits of the new game farming regime. Landowners, on the other hand, indicated financial gains from the land use change. The transition therefore resulted in trade-offs that surfaced as social, economic, and cultural losses and gains. These changes, especially in social relationships and community structures, have implications for resilience and possible future pathways of development in the region.